Application of Game-Based Outdoor Learning to Mathematical Spatial Ability - Indah Nur Rohmah; Sofnidar Sofnidar; Khairul Anwar (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
The majority of students have very low levels of spatial thinking ability. Spatial ability is essential for students to better understand geometry topics, particularly polyhedra (solid figures with flat faces). This condition is further exacerbated by the use of conventional mathematics teaching methods, which primarily focus on lectures, textbooks, and drill exercises. As a result, classroom learning often leads students to feel bored and less enthusiastic. To address this issue, the researcher implemented a game-based outdoor learning approach. Therefore, this study aims to examine the improvement in the mathematical spatial ability of ninth-grade students after the implementation of game-based outdoor learning. The research subjects were students of class IX B at one junior high school in Jambi City. This study employed a quantitative descriptive pre-experimental method, using a One-Group Pretest–Posttest Design, in which only one experimental class was given the treatment. To determine the level of improvement in students’ mathematical spatial ability, N-gain analysis was used. The N-gain value was calculated by comparing the difference between pretest and posttest scores, and the results were interpreted into high, moderate, or low improvement categories. Based on descriptive statistical analysis, the research data showed that the minimum student score was 20, the maximum score was 86.6, and the mean score of students’ mathematical spatial ability was 56.6357, with a standard deviation of 17.44458. Out of 28 students, 3 students showed a high improvement in spatial ability, 20 students showed moderate improvement, and 5 students showed low improvement. The implementation of game-based outdoor learning was found to enhance students’ spatial ability, particularly in the geometry of polyhedra, by integrating physical and collaborative activities to achieve enjoyable learning objectives.